If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -7 = -43 + 6z Reorder the terms: -7 + 2z = -43 + 6z Solving -7 + 2z = -43 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. -7 + 2z + -6z = -43 + 6z + -6z Combine like terms: 2z + -6z = -4z -7 + -4z = -43 + 6z + -6z Combine like terms: 6z + -6z = 0 -7 + -4z = -43 + 0 -7 + -4z = -43 Add '7' to each side of the equation. -7 + 7 + -4z = -43 + 7 Combine like terms: -7 + 7 = 0 0 + -4z = -43 + 7 -4z = -43 + 7 Combine like terms: -43 + 7 = -36 -4z = -36 Divide each side by '-4'. z = 9 Simplifying z = 9
| 5b-3b=8-2b | | 2x-7=-43+6x | | 4x-25+75=180 | | (3x+1)+(2x-1)+40=180 | | 2x^2+12x-122= | | 2(5x+1)-3(2x+3)=5 | | 3(x+4)+21(x-4)=14 | | 4x^3+12x^2-18x= | | 3.4x=8 | | Y=-16t^2+80t+4 | | x-0.7=9.42 | | -1+3x=x-5 | | 9x^3+30x-24= | | 6.2x-3+x-1.7= | | x^3+5x^2-20x= | | 37s=-333 | | -18x^3-6x^2= | | 2j+-1=2 | | (3x+1)+(2x+1)+40=180 | | -2x+28= | | 2y+3x(x+1)=y | | 23+3x(x+1)=y | | 72x^5+18x^2= | | f=4(-x)+6 | | 6+ln(x)=4 | | (3)(-6)= | | Ln(x)=3.2958 | | 7n^2+23+6n=0 | | 10(x+2)=7 | | Lnx=3.2958 | | (x+3)x(x-7)=0 | | 15-7=50 |